عقبات تطبيق التدريس التواصلي للغة - CLTفي المدارس الابتدائية الليبيةــ منظور ريفـــي - Al-Mashloukh, Bernia Hussein Al-Mukhtar (مجلة الاصالة, 2025)
Despite the critical demand for advanced English proficiency in Libyan higher education, primary public schools, particularly in rural areas, have been neglected. This qualitative study investigates the imperative for implementing improved methodologies in Teaching English as a Foreign Language (EFL) in Libyan primary public schools, using the post-conflict rural municipality of Al Gwaleesh as a case study. Data were collected by questionnaires and classroom observations from ten teachers and ten thirdyear pupils. The findings reveal a systemic reliance on traditional GrammarTranslation Methods, a stark deficiency of resources (including basic teaching aids and ICT), and minimal student engagement. Teachers demonstrated limited application of Communicative Language Teaching (CLT) principles, focusing predominantly on rote memorization and written exercises. Consequently, pupils reported low motivation and a failure to grasp the language's practical utility. The study concludes that a fundamental overhaul of EFL pedagogy in Libya is urgently required, recommending the integration of audio-visual aids, activity-based learning, and strategic incorporation of Information and Communication Technologies (ICTs) to foster intrinsic motivation and build a sustainable foundation for English proficiency.